ON THE FEATURES OF THE WORK OF A FINITE ACOUSTIC ANTENNA FORMED BY FREE-FLOODING CYLINDRICAL TRANSDUCERS - Basovsky, V.G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
The problem of sound radiation by a finite antenna array formed by free-flooding cylindrical transducers with flanges is considered. Two variants for the antenna array are considered: the same electrical voltage is supplied to the electrodes of all transducers and a different voltage is applied to them in order to equalize the oscillatory speeds of the transducers. Numerical data for the basic electrical, mechanical and acoustic characteristics of the antenna array are analyzed, taking into account the acoustic interaction of the transducers.